BEING AWARE OF SPECIALIZATION THROUGH TERMINOLOGY - Abdinazarov Xasan Shaymanovich (Modern American Journals, 2025)
In teaching and learning engineering English, the learners and teachers feel often difficulties in understanding the terms of that field of expertise. Consequently, adult learners need to acquire specialization in both English and Uzbek languages. Besides, they should have fundamental knowledge in studying subject matter in English because of better comprehending the technical contexts which is full of terms. Therefore, adult learners seek to find better knowledge by reading texts and making analysis in interpretation the whole meaning of the text. This paper highlights discussions of scholars on the issues of corpus linguistics, especially, analysis of collocations, tokens and types occurred in authentic context.
Keywords: frequency words, authentic context, tokens and types